IMPLEMENTASI MODEL THINK TALK WRITE (TTW) DALAM PENINGKATAN HASIL BELAJAR SISWA MATERI PROCEDURE TEXT - Lies Muhsonati (Discovery, 2023)
The purposes of this study are to describe (1) the implementation of the Learning Implementation Plan during the learning process, (2) the learning outcomes of the product after the implementation of Think Talk Write, (3) student activities during the implementation of the Think Talk Write, and (4) students' responses to learning by applying the Think Talk Write learning model. This classroom action research was carried out for two cycles in class X MIPA 2 SMA Negeri 1 Puri involving 35 students. Each cycle consists of stages of planning, implementation, observation and reflection. The results showed that (1) the learning process by applying the Think Talk Write learning model could be carried out in good categories, namely in the first cycle with a value of 3.03 and the second cycle of 3.27., (2) student activities during the application of the Think Talk Write learning model showed students active with an activeness of 87.15% in the first cycle and 93.48% in the second cycle, (3) character behavior in both cycles showed good behavior with an average score of 3.23 (good) in the first cycle and 3.45 (good) in the second cycle, (4) results student learning after the implementation of the Think Talk Write learning model has increased with the percentage of completeness 77.14% in the first cycle increasing to 91.4% in the second cycle, and (5) student responses to learning by applying the Think Talk Write learning model are positive